Paradigm change in Pentateuchal research - Paradigm Change in Pentateuchal Research 2017 Riehen; Armgardt, Matthias 1968-; Kilchör, Benjamin 1984-; Zehnder, Markus 1964- (Wiesbaden Harrassowitz Verlag, 2019)
Cover -- Title Pages -- Imprint -- Table of Contents -- Preface -- I. Introductory and Methodological Contributions -- Georg Fischer: Time for a Change -- Richard E. Averbeck: Reading the Torah in a Better Way -- Joshua Berman: The Limits of Source Criticism -- Koert van Bekkum: The Divine Revelation of the Name -- II. Legal History -- Matthias Armgardt: Why a Paradigm Change in Pentateuch Research is Necessary -- Guido Pfeifer: The Pentateuch Paradigm and Ancient Near Eastern Legal History -- Benjamin Kilchör: Wellhausen's Five Pillars for the Priority of D over P/H: Can They Still Be Maintained? -- Markus Zehnder: Leviticus 26 and Deuteronomy 28 -- III. Torah and Prophets -- Eckart Otto: Deuteronomy as the Legal Completion and Prophetic Finale of the Pentateuch -- Kenneth Bergland: Jeremiah 34 Originally Composed as a Legal Blend of Leviticus and Deuteronomy 15 -- Carsten Vang: The Non-Prophetic Background for the King Law in Deut 17:14-20 -- IV. Dating Issues -- Hendrik J. Koorevaar: Steps for Dating the Books of the Pentateuch -- Lina Petersson: The Linguistic Profile of the Priestly Narrative of the Pentateuch -- Jan Retsö: The Tabernacle and the Dating of P -- John S. Bergsma: A 'Samaritan' Pentateuch? -- Sandra Richter: What's Money Got to Do with It? -- Pekka Pitkänen: Reconstruction the Social Contexts of the Priestly and Deuteronomic Materials in a Non-Wellhausian Setting -- Index of Ancient Sources -- Index of Modern Authors.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Konferenzschrift -- 2017 -- Riehen, Basel